Teaching Mathematics to Hearing Impaired Students In An Inclusive Classroom In Swat Pakistan - Sharif Ullah, Musarrat Habib (JSE, 2023)
Abstract The primary objective of this study was find the effect of “Total communication technique” for the teaching of mathematics to the hearing impaired students and differentiate the learning outcomes of these learners in an inclusive education classroom. T